Epidemiological Study of Cystic Echinococcosis in Sheep, Cattle and Goats in Erbil Province - Hassan, Zuber I.; Mero, Wijdan Wijdan; Casulli, Adriano; Interisano, Maria; Boufana, Belgees (Science Journal of University of Zakho, 2016)
Cystic echinococcosis (CE) or hydatid cyst (HC) caused by the larval stage of the tapeworm Echinococcus granulosus continues to be a substantial cause of morbidity and mortality in many parts of the world. Since Kurdistan region is considered as endemic area, an epidemiological study was conducted to investigate the occurrence of CE isolated from sheep, cattle and goats from July 2013 to June 2014. The total rate of infection was 11.17(457/4092), with the highest rate (9.07%) in sheep and the lowest (0.54%) in goats. Regarding the sex of the infected animals, female showed slightly a higher rate than males (5.99% versus 5.18%) which statistically non-significant (P>0.05). Among the three intermediate host sheep showed the highest rate of infection (14.51%) regarding the sex females of sheep and cattle showed higher rate of infection versus males (27.36 and 20.35 versus 9.37 and 3.86). Furthermore, the highest incidence of CE in sheep, cattle and goats were found among the age group over three years (18.75, 5.41 and 1.69%, respectively), while the lowest rate was noted in the age groups less than one year (3.96 and 0.25%, o.33, respectively). On the other hand, sheep showed high rate of infection throughout the year with peaks during May to July which were 19.44%, 17.59 and 18.14%,respectively. This was followed by cattle and goats (11.67% and 5.26%) in April and December, respectively. Regarding the size, the higher numbers of small sized cysts were found in the liver (98/175), while the highest numbers of large sized cysts were found in both liver and lung which were 69/165. The liver and lungs appeared to be the site of predilection, since highest rate of infection was reported in these organs. Regarding the fertility of CE, the highest was in sheep (87.6%), followed by goats (77.27%) and then the cattle (40.63%).